Production of ferulic acid from banana stem waste by using co-culture - Nur Syahirah , Mohd Shkuri (2015)
Ferulic acid (FA) or known as (E)-3-(4-hydroxy-3-methoxy-phenyl) prop-2-enoic acid is a type of caffeic acid derivative. It is widely found in vegetables, fruits and some beverages such as beer and coffee. The abundance of these aromatic compounds in plant materials combine with known microbial transformation made them attractive for biotransformation research. Therefore production of FA by co-culture was a main focus in this study. This research study consists of two objectives. First objective was to perform growth profile for co-culture and produce FA from banana stem waste, thus test for the best producer. Second objective was to perform kinetic study of FA production by using co-culture. Possibility of using cheap materials in this research study had been proven as the co-culture was isolated from soil and banana stem waste (BSW) as the substrate. The method for this research study was divided into six steps. Firstly, substrate was prepared by collecting BSW at Gambang, Pahang, Malaysia. Then, the inoculum for pure culture was prepared to perform the fermentation process. After 24 hours of fermentation, they were ready for the analysis by using HPLC. Based on the analysis, six best producers from pure culture were determined as the best producers which are bacteria Bacillus thuringiensis strain NRBC101235 (A), Brevibacillus formosus (B), Bacillus pumilus SAFR-032 (C), Bacillus cereus strain JCM 2152 (D), Lysinibacillus fusiformis strain NRBC15717 (E) and Bacillus cereus strain ATCC14579 (F). Then, growth profiles for pure culture and co-culture were carried out by using indirect method. From the growth profile result, two sets of inoculum for co-culture were prepared and injected into substrate at their stationary phase. The co-culture was from combination of bacteria ABEF and BCDEF. Then, fermentation process began. From the analysis, the set of co-culture BCDEF was identified as the best producer. They were able to produce FA from the range of 2.0 to 3.0 mg/g. According to the previous research, the concentration of FA should be from the range of 1 to 3 mg/g. Kinetic study for co-culture BCDEF was carried out. The hyperbolic equation proposed by Monod which modified by Lawrence and McCarty was used to describe microbial growth and biodegradation process. In order to solve the equation, the values of kinetic parameters which are Ks, qmax and Y were calculated by using Runge-Kutta Fourth method. The values obtained were 0.9 g/L, 0.1669 mmol/cell.h and 0.8077 g/g respectively with R-squared value for substrate and biomass were 0.8538 and 0.8833 each. Hence, FA was successfully produced from banana stem waste by using co-culture.